Paediatric retinal detachment: aetiology, characteristics and outcomes - McElnea, Elizabeth (Int J Ophthalmol, 2018)
AIM: To provide contemporary data on the aetiology, clinical features and outcomes of paediatric retinal detachment. METHODS: A retrospective review of all those under 16y who underwent surgical repair for retinal detachment at a single centre between the years 2008 and 2015 inclusive was performed. In each case the cause of retinal detachment, the type of detachment, the presence or absence of macular involvement, the number and form of reparative surgeries undertaken, and the surgical outcome achieved was recorded. RESULTS: Twenty-eight eyes of 24 patients, 15 (62.5%) of whom were male and 9 (37.5%) of whom were female, their mean age being 11.6y and range 2-16y developed retinal detachment over the eight year period studied. Trauma featured in the development of retinal detachment in 14 (50.0%) cases. Retinal detachment was associated with other ocular and/or systemic conditions in 11 (39.3%) cases. A mean of 3.0 procedures with a range of 1-9 procedures per patient were undertaken in the management of retinal detachment. Complex vitrectomy combined with scleral buckling or complex vitrectomy alone were those most frequently performed. Mean postoperative visual acuity was 1.2 logMAR with range 0.0-3.0 logMAR. In 22 of 26 (84.6%) cases which underwent surgical repair the retina was attached at last follow-up. CONCLUSION: Aggressive management of paediatric retinal detachment including re-operation increases the likelihood of anatomical success. In cases where the retinal detachment can be repaired by an external approach alone there is a more favourable visual outcome.